Elevated ectodomain of type 23 collagen is a novel biomarker of the intestinal epithelium to monitor disease activity in ulcerative colitis and Crohn's disease. Issue 2 (29th March 2021) - Manon‐Jensen, T.; Sun, S.; Lindholm, M.; Domislović, V.; Giuffrida, P.; Brinar, M.; Mazza, G.; Pinzani, M.; Krznarić, Z.; Di Sabatino, A.; Karsdal, M. A.; Mortensen, J. H.
Abstract: Background: Impaired intestinal epithelial barrier is highly affected in inflammatory bowel disease. Transmembrane collagens connecting the epithelial cells to the extracellular matrix have an important role in epithelial cell homeostasis. Thus, we sought to determine whether the transmembrane type 23 collagen could serve as a surrogate marker for disease activity in patients with Crohn's disease and ulcerative colitis. Methods: We developed an enzyme‐linked immunosorbent assay to detect the ectodomain of type 23 collagen (PRO‐C23) in serum, followed by evaluation of its levels in both acute and chronic dextran sulphate sodium colitis models in rats and human inflammatory bowel disease cohorts. Serum from 44 Crohn's disease and 29 ulcerative colitis patients with active and inactive disease was included. Results: In the acute and chronic dextran sulphate sodium‐induced rat colitis model, the PRO‐C23 serum levels were significantly increased after colitis and returned to normal levels after disease remission. Serum levels of PRO‐C23 were elevated in Crohn's disease ( p < 0.05) and ulcerative colitis ( p < 0.001) patients with active disease compared to healthy donors. PRO‐C23 differentiated healthy donors from ulcerative colitis (area under the curve [AUC]: 0.81, p = 0.0009) and Crohn's disease (AUC: 0.70, p = 0.0124). PRO‐C23 differentiated ulcerative colitis patients with active disease from those in remission (AUC: 0.75, p = 0.0219) and Crohn's disease patients with active disease from those in remission (AUC: 0.68, p = 0.05). Conclusion: PRO‐C23 was elevated in rats with active colitis, and inflammatory bowel disease patients with active disease. Therefore, PRO‐C23 may be used as a surrogate marker for monitoring disease activity in ulcerative colitis and Crohn's disease. Key Summary: Summarise the established knowledge on this subject Intestinal permeability in Crohn's disease (CD) and ulcerative colitis (UC) is impaired, which results in the invasion of numerous bacteria, followed by immune cell infiltration to the gut. Increased tissue remodelling and loss of epithelial integrity are related to flares in CD and UC. Type 23 collagen is a transmembrane collagen and is expressed by intestinal epithelial cells and is therefore a marker of epithelium integrity. What was the significant and/or new findings of this study? A novel type 23 collagen marker was developed, quantifying the ectodomain of type 23 collagen (PRO‐C23) in serum. Elevated serum levels of PRO‐C23 was demonstrated to be associated with dextran sulphate sodium (DSS) colitis rats (acute and chronic) and CD and UC patients with active disease. PRO‐C23 may potentially be used as a non‐invasive surrogate of disease activity in CD and UC patients and thus aid in diagnosing and monitoring patients.